The in vivo metabolism of 5-(4-nitrophenyl)-4-phenyl-2,4-dihydro-3h- 1,2,4-triazole-3-thione in rats - (:unkn) unknown (Freund Publishing House Ltd, 1999)
It is known that substituted 1,2,4-triazole-3-thione derivatives have several biological activities, such as antimicrobial, diuretic and antidepressant activities. In our previous studies, the antifungal activity of 5-(4-aminophenyl)-4-phenyl-2,4-dihydro-3H-1,2,4-triazole-3-thione was found to be active against Candida tropicalis K1022. The aim of this study was to investigate the in vivo metabolic pathway of 5-(4-nitrophenyl)-4- phenyl-2,4-dihydro-3H-1,2,4-triazole-3-thione which was selected as a model compound for this study. The substrate and its potential metabolites, i.e. the acetylation and nitro reductive products, were synthesized and then separated using HPLC on a reverse phase system. In the in vivo metabolism study, a 4 mg dose was administered i.p. to male Wistar rats. Blood samples were collected at 0, 2, 4, 8, 12, 24 and 56 hours after administration and were passed through a Sep-Pak cartridge. The acetylated metabolite [5-(4- acetylaminophenyl)-4-phenyl-2,4-dihydro-3H-1,2,4-triazole-3-thione], the amine metabolite [5-(4-aminophenyl)-4-phenyl-2,4-dihydro-3H-1,2,4-triazole- 3-thione] and an unknown metabolite were detected.
Keywords: 1,2,4-triazoline-3-thione; In vivo metabolism; Rat